2018
DOI: 10.1016/j.jphys.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Standard restrictive sternal precautions and modified sternal precautions had similar effects in people after cardiac surgery via median sternotomy (‘SMART’ Trial): a randomised trial

Abstract: Australian and New Zealand Clinical Trials Registry ANZCTRN12615000968572. [Katijjahbe MA, Granger CL, Denehy L, Royse A, Royse C, Bates R, Logie S, Nur Ayub MA, Clarke S, El-Ansary D (2018) Standard restrictive sternal precautions and modified sternal precautions had similar effects in people after cardiac surgery via median sternotomy ('SMART' Trial): a randomised trial. Journal of Physiotherapy 64: 97-106].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 33 publications
3
46
0
2
Order By: Relevance
“…Data were collected from nested studies within two randomized controlled trials (published previously). 6,1214 Reliability analyses data were from four different subgroups of participants within a multisite observational study (Table 1). Test–retest reliability was measured in 55 participants for single raters, and similar raters were used in Victoria’s Southern Health and Melbourne Health (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were collected from nested studies within two randomized controlled trials (published previously). 6,1214 Reliability analyses data were from four different subgroups of participants within a multisite observational study (Table 1). Test–retest reliability was measured in 55 participants for single raters, and similar raters were used in Victoria’s Southern Health and Melbourne Health (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…6 These are reported in prior publications outlining the study protocol. 6,1214 As part of the original trials, participants also completed several other outcome measures (physical function, pain and health-related quality of life) at hospital discharge, four weeks and three months postoperatively. For this pyschometric investigation, data from all participants from the original trials were pooled and included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Second, the ERAS Cardiac guidelines include no specific recommendations for early postoperative enteral feeding and mobilization, even though these measures are known to work together to stimulate resumption of gut function, preserve musculoskeletal function, and promote a faster and safer return to normal activities after surgery. [17][18][19][20][21][22] A sternotomy incision limits early mobilization and rehabilitation activities. Although the ERAS Cardiac guidelines do recommend that cardiac surgery programs develop multidisciplinary institutional guidelines to address early feeding and mobilization, 14 traditional sternal precautions prioritize the stability of the bony union over patient mobility, greatly limiting opportunities for return to normal activity and physical rehabilitation in the postoperative recovery period.…”
Section: Enhanced Recovery After Cardiac Surgerymentioning
confidence: 99%
“…14 Findings from a recent study demonstrated that various upper limb tasks performed by patients within the safe limits of pain and discomfort after median sternotomy resulted in minimal bone motion with no adverse events. 15 Second, seat belt forces and airbag deployment may damage the healing sternum during a motor vehicle crash. Unquestionably, there are documented accounts of sternal fractures from motor vehicle accidents 16 associated with the use of seat belts 17 and the deployment of airbags.…”
mentioning
confidence: 99%